PCI of chronic total occlusions: what is the clinical benefit and impact on quality of life?. (3rd October 2022) - Costa, H; Martins, J; Mota, T; Santo, M E; Fernandes, R; Carvalho, D; Palmeiro, H; Bispo, J; Franco, P; Marto, S; Guedes, J; Marreiros, A; et al.
Abstract: Introduction: Coronary chronic total occlusions (CTO) are relatively common findings in the context of coronary angiography. The indication for revascularization of this type of lesions remains controversial. The recommendations of international cardiology societies consider the treatment of CTO by percutaneous coronary intervention (PCI) in selected patients, but this technique is not yet widely used in this context. Objectives: To evaluate the clinical and quality of life impact of patients undergoing PCI-CTO, including angina, heart failure (HF), acute myocardial infarction (AMI), mortality and improved quality of life (QoL) after the procedure. Methods: Retrospective study for biennium 2019/2020, composed of n=177 patients undergoing PCI-CTO. A descriptive and comparative analysis of the sample regarding the demographic and clinical characteristics of patients was performed, to whom a quality of life questionnaire (WHOQOL-Brief) was applied. The descriptive analysis was based on means and standard deviations and on the analysis of statistical tests, t-Student and Mann-Whitney were performed according to the parametric and non-parametric context, respectively. Results: A total of 177 patients were identified, with a mean age of 65.7±11.2 years, 51.5% female. 75% of patients showed high blood pressure, 39% diabetes and 80.5% NSTEMI. At 30 days after PCI only 21% of patients had symptoms (angina or HF), with clinical improvement at 180 days to 10% symptomatic. Regarding QoL, an average score of 4.3 (maximum of 5) was obtained for the 2 questions that independently assess the patient's perception of their QoL after the procedure. High levels of scores were also obtained by domains (QoL>70%), with marked improvement in the Physical, Environmental and Psychological domains, becoming more evident in the latter at 30 days after the procedure in patients who remained asymptomatic (75.2%, p=0.023). This benefit was accompanied by improvement in left ventricular function (LVEF), being more evident in asymptomatic patients and without events after procedure. Mortality and AMI occurred in 6% and 2%, respectively. Conclusion: The majority of patients had clinical benefit and expressed improvement in QoL after undergoing PCI-CTO, which was accompanied by improvement in LVEF, reinforcing the usefulness of the technique and the approach of this type of lesions in selected patients. Funding Acknowledgement: Type of funding sources: None.